Impoliteness Addressed to Different Genders and their Responses in The Kitchen Nightmares, a TV Reality Show - Milal, A. Dzo'ul; Pramono, Angga Cahya (Journal of Pragmatics Research, 2021)
This paper reveals the impoliteness strategies addressed to different genders and their corresponding responses. The data source is the video transcript of a TV reality show, The Kitchen Nightmares season 6 episode 2 for substantial and technical considerations. As it contains impolite expressions, abundant data can be gained to clarify the focal points. The subjects are the host and male and female participants in that show. This study uses a descriptive qualitative approach. In collecting the data, the researcher identifies the utterances containing impoliteness and their responses in the transcript. Then, they are classified and compared to discover the impoliteness strategies and their responses related to gender differences. It is discovered that, in this show, the types of impoliteness strategies addressed to male addressees are not different from those of female participants. Regarding responses, it is found out that male participants respond to the impoliteness differently from the females. It can be concluded from the show that gender difference is not effective as recipients of impoliteness, but it is operative as producers of the response towards impoliteness. Keywords: entertainment, gender, impoliteness, responses to impoliteness